Evaluation of the protective effect of paricalcitol and vitamin D3at doxorubicin nephrotoxicity in rats with99mTechnetium-dimercaptosuccinic acid renal scintigraphy and biochemical methods - Demir, Fadime; Demir, Mustafa; Aygun, Hatice (Sage Publications Ltd, 2021)
Aim: The present study aimed to examine the effect of paricalcitol (PRC) and vitamin D-3(vit D-3) on doxorubicin (DOX)-induced nephrotoxicity in rats. Materials and Methods: Forty-two Wistar rats were randomly categorized into six groups: control; 2) PRC(0.5 mu g/kg) and 3) vit D-3(5.000 IU/kg) administered for 14 days; 4) DOX, 18 mg/kg administered on the 12th, 13th and 14th days of the study; 5) PRC (0.5 mu g/kg, +DOX(18 mg/kg); vit D(3()5.000 IU)+DOX(18 mg/kg). On the 15th day of the experiment,Tc-99m-DMSA uptake level and biochemical parameter in serum and tissue were assay. Results: Activities of(99m)Technetium-Dimercaptosuccinic Acid (Tc-99m-DMSA) were lower in groups receiving DOX and/or PRC+DOX, vit D-3+DOX than in control groups. The(99m)Tc-DMSA level in the group PRC+DOX and vit D-3+DOX were importantly higher than DOX group. DOX caused an important increase in blood urea nitrogen (BUN), creatinine, Tumor Necrosis Factor-alpha(TNF- alpha), interleukin-6(IL-6) and nitric oxide(NO) levels compared to control groups. However, PRC and vit D(3)pretreatments lowered them. Uptake of(99m)Tc-DMSA level was higher in groups PRC+DOX than in vit D-3+DOX group. Administration of PRC and vit D(3)alone did not change alterations all of parameters. Conclusion: The results indicated that PRC administration protects kidney in DOX-induced nephrotoxic rats. In addition, PRC has a stronger nephroprotective effect than vit D-3.
Keywords: Doxorubicin; paricalcitol; vitamin D-3; rat; kidney; nephrotoxic